A Comparative Study of Improvised Manual Vacuum Aspiration Versus Pipeline Sampling for Endometrial Sampling - Baqai, Shehla; Nawaz, Qudsia; Tufail, Shazia; Tabassum, Humaira; Nasreen, Samia; Nayyer, Shazia (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the safety and efficacy of Improvised S2Q manual vacuum aspiration and Pipelle sampling as a diagnostic procedure for the evaluation of women presenting with abnormal uterine bleeding. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Obstetrics and Gynecology, Combined Military Hospital, Lahore Pakistan, from Oct 2021 to Aug 2022. Methodology: A total of 148 females over 35 years of age with abnormal uterine bleeding, who needed endometrial sampling, were divided into two groups of 74 participants each. Group-A underwent endometrial sampling by Improvised S2Q manual vacuum aspiration, while Group-B underwent endometrial sampling by Pipelle sampler. Results: Mean age of patients was 47.36±8.34 years in Group-A and 48.20±8.96 years in Group-B, while the mean BMI was 30.59±4.67 kg/m2 and 27.39±2.50 kg/m2 in Groups A and B, respectively. The volume of specimen obtained was found to be higher in the Improvised S2Q manual vacuum aspiration-Group as compared to the pipeline sampling-Group. The operating time in the Improvised S2Q manual vacuum aspiration-Group was 3.37±0.49 minutes, while in the pipeline sampling-Group, it was 3.20±0.55 minutes. No difference was found in the two procedures for side effects (tachycardia, pain/cramps) and complications (significant blood loss, perforation, infection), added analgesia or histopathology report. Conclusion: Improvised S2Q manual vacuum aspiration can be used as an alternative low-cost procedure for endometrial sampling in women with abnormal uterine bleeding. Keywords: Biopsy, Curettage, Endometrium, Manual vacuum aspiration, Pipeline sampling.